A census of cool-core galaxy clusters in IllustrisTNG - Barnes, David J.; Springel, Volker; Pillepich, Annalisa; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The thermodynamic structure of hot gas in galaxy clusters is sensitive to astrophysical processes and typically difficult to model with galaxy format
Gesehen am 25.01.2019